Learning communities: a trend for 2013 - Sanz-Martos, Sandra (Anuario ThinkEPI, 2013)
Three types of communities are defined: learning, interest and practice. Their characteristics, operation, commonalities and differences are discussed.
Keywords: Learning communities; Communities of interest; Communities of practice; Methodologies; Research; Troubleshooting; Education; Training; Teaching.